76.4k views
0 votes
Solve 2y – 3 = 4y + 6.

User DeRagan
by
6.0k points

2 Answers

6 votes

Answer:

y = - 9/2

Explanation:

2y - 3 = 4y + 6

-6 -6 *subtract 6 from both sides of the equation, which is the opposite operation

2y - 9 = 4y * your sixes cancel out leaving you w/ the current equation; next you subtract 2y from each side.

2y - 9 = 4y

-2y -2y

* now you are left with: -9 = 2y; so you do the opposite operation (again) and divide both sides by 2. Your twos cancel out leaving you with y = -9/2.

User Adam Goodwin
by
5.4k points
4 votes
2y - 3 = 4y + 6
Add 3 to both sides
2y - 3 + 3 = 4y + 6 + 3
2y = 4y + 9
Subtract 4y from both sides
2y - 4y = 4y - 4y + 9
Simplify,
-2y = 9
Then, divide bot sides by -2
-2y/-2 = 9/-2
Simplify,
y = -9/2
User Tarra
by
5.6k points